Rising External Debt and Diminishing Exports: Concurrent Constraints to Economic Progress in Nigeria - Ugbaka, Malachy Ashywel; Abuh-Amasi, Scholastica A.; Ndome, Joseph Nsabe (International Journal of Economics and Financial Issues, 2022)
The country's strong reliance on oil and gas exports exposes it to the considerable risk of global oil market instability, as external debt continues to rise as exports fall, more attention is being paid to the consequences of this trend. The major goal of this paper is to determine Nigeria's rising external debt and declining exports, using an autoregressive distributed lag (ARDL) model, we investigated Nigeria's rising external debt and declining exports using annual time series data from 1986 to 2020. In the short run across the study period, the study reveals evidence of a negligible beneficial impact of both external debt and export on economic growth meaning that in the short run, both foreign debt and export have a negligible beneficial impact on economic growth, according to the estimates in Nigeria, in reality, in the long run, the impact is negative, with exports having a greater negative impact than foreign debt, as a result, the paper submits that Nigeria's economy is at a fork in the road, based on these findings, it is suggested that external borrowing be restricted until current debt stocks are repaid, that external loans be tied to specific projects to avoid inefficient fund allocation, that domestic capital markets be explored as an alternative to external borrowing, that more export diversification be undertaken to mitigate poor performance of primary commodity exports, and that commodity exchanges be established to attract more speculators, external borrowing should be limited until current debt stocks are serviced in order to achieve economic growth.